Analisis Kesalahan Siswa Bergaya Kognitif Reflektif dalam Pemecahan Masalah Kontekstual - Ucik Fitri Handayani; Mukhtamilatus Sa’diyah; Lailatul Anggraini (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA DAN SAINS, 2025)
There are several mistakes made by students in solving mathematical problems. Students' mistakes are also influenced by cognitive style. The purpose of this study is to describe the mistakes made by students with reflective cognitive styles in solving contextual problems. This study is a descriptive study with a qualitative approach conducted at MA Mambaul Ulum Banjarejo. The material used in this study is linear programming. Data collection was carried out through written tests and interviews with each subject. The instruments used in this study were (1) the MFFT (Matching Familiar Figures Test) cognitive style test, (2) a linear programming problem-solving ability test, and (3) interview guidelines. There were two students with reflective cognitive styles as subjects in this study. The analysis of student errors was based on Newman's Theory. The results of this study are [1] both students with reflective cognitive styles made different mistakes, one student made conceptual errors, namely incorrect determination of inequality signs and transformations, and the other made procedural errors, namely the student was unable to continue working on the problem-solving process and also made mistakes in the transformation stage, process skills, and writing the final answer. [2] Both students with reflective cognitive styles also made the same errors; both made errors in the process skill stage and in the final answer writing stage.